Reducing iodinated contrast volume by manipulating injection pressure during coronary angiography. Issue 5 (7th January 2014) - Kaye, David M.; Stub, Dion; Mak, Vivian; Doan, Tuan; Duffy, Stephen J.
<x xml:space="preserve">Abstract</x> Objective To evaluate the impact of a device‐mediated modification of the injection pressure profile on iodinated contrast volumes during coronary angiography and percutaneous coronary intervention (PCI). Background The development of iodinated contrast‐induced acute kidney injury (AKI) is associated with significant morbidity and mortality in patients undergoing coronary angiography and intervention, particularly in the setting of ST‐elevation myocardial infarction. Iodinated contrast volume is a recognized risk factor for iodinated contrast‐induced AKI. Mitigation of iodinated contrast loss due to coronary iodinated contrast reflux represents a potential means to reduce iodinated contrast volume. Method and Results We assessed the effectiveness of injection pressure modulation using an iodinated contrast conservation system (CCS), in 21 patients undergoing diagnostic coronary angiography or PCI. System activation was associated with a marked reduction in iodinated contrast injection compared with standard imaging (3.5 ± 1.1 vs. 5.4 ± 1.7 mL, P < 0.001). Paired images were obtained in 59 instances with significantly less iodinated contrast use with CCS use (3.3 ± 1.1 vs. 5.5 ± 1.6 mL, P < 0.001), with comparable image quality in 98% of cases. Conclusions Modulation of iodinated contrast injection pressure provides a novel potential means to reduce iodinated contrast volumes by attenuating inefficient losses due to ostial reflux. Future studies are required to define the ability of the CCS to reduce total iodinated contrast volume and to impact upon the risk of iodinated contrast‐induced AKI. © 2013 Wiley Periodicals, Inc.